Prison Library Services in Croatia Need Improvement to Meet International Standards of Universal Rights to Access - Perryman, Carol L. (Evidence Based Library and Information Practice, 2016)
A Review of: Šimunić, Z., Tanacković, S.F., & Badurina, B. (2016). Library services for incarcerated persons: A survey of recent trends and challenges in prison libraries in Croatia. Journal of Librarianship and Information Science, 48(1), 72-89. http://dx.doi.org/10.1177/0961000614538481 Objective – To compare the status of prison libraries in Croatia to prior studies and ultimately, to guidelines for prison library services (Lehmann & Locke, 2005). Two research questions were asked: 1) How are Croatian prison libraries organized and managed? and 2) What kind of library collections and services are offered to incarcerated persons in Croatia? Design – Quantitative survey. Setting – 23 Croatian prison libraries. Subjects – Persons in charge of prison libraries. Methods – A paper survey was mailed to all 23 Croatian prisons in 2013. The survey consisted of 31 questions grouped into 3 categories: general library information, management of the library, and use. Analysis provided descriptive statistics. Main Results – Twenty-one responses (91%) were received. For the 10 institutions providing data on library holdings size, the numbers ranged from 450 to 6122, but per capita figures were not possible to calculate as no responses provided prison population size. Most (65%) maintained an entry book for new acquisitions, while one library kept a card catalogue. Half performed collection assessment on an annual basis. While all but 1 of the prisons had libraries, most (16 of 20) reported that funding was not provided on a regular basis; 13 had space allocated specifically for library purposes, but none were staffed by trained librarians, instead using prison staff or prisoners. Only two libraries practised regularly-scheduled collection development, with half acquiring materials solely through donations resulting in limited topical coverage. All collections included monographs, but only around 25% carried newspapers, magazines, music, or videos. While use of the libraries was high, most responses reflected severely limited educational, rehabilitative or cultural programming and access to the internet, and lack of space for collections and reading purposes. Conclusion – Libraries in Croatia fail to meet international standards for staffing, collections, and services. Recommendations for immediate improvement are made, including legislative advocacy and funding, improved public library involvement, and the creation of national standards aligned with international standards.